Efficacy and safety of TACE combined with TKIs and PD-1 inhibitors in HCC patients with prior TIPS - Xiong, Kai; Huang, Kuiyuan; Liu, Yulong; Pang, Huajin; Chen, Peng; Zheng, Yalu; Li, Tengzheng; Li, Zhangyun; Zhang, Moran; Zheng, Dandan; Huang, Xiaohong; Cao, Mingrong; et al. (Frontiers in Oncology, 2025)
PurposeTo compare the efficacy and safety of TACE combined with TKIs and PD-1 inhibitors between HCC patients with and without prior TIPSMethodsThis retrospective propensity score matching (PSM) study included advanced HCC patients treated with prior TIPS followed by TKIs, PD-1 inhibitors, and TACE between January 2021 and January 2023. Patients were matched with a control group of HCC patients who had not undergone TIPS (non-TIPS). Outcome measures included objective response rate (ORR) using modified RECIST (mRECIST v1.1), disease control rate (DCR), progression-free survival (PFS), overall survival (OS), and safety assessed by CTCAE v5.0.ResultsA total of 172 patients were included before PSM. After PSM, 42 patients with prior TIPS were matched with 71 non-TIPS patients. ORR was 31.0% in the TIPS group and 57.7% in the non-TIPS group (p = 0.007), Both PFS and OS were longer in the non-TIPS group, with a median PFS of 7.9 months for TIPS patients versus 12.3 months for non-TIPS patients (hazard ratio [HR] = 2.253, p < 0.001), and a median OS of 13.5 months versus 21.1 months, respectively (HR = 2.282, p = 0.002). Treatment-related adverse events showed no significant differences between the two groups.ConclusionTACE combined with TKIs and PD-1 inhibitors showed lower efficacy in HCC patients with prior TIPS, but it remains a viable option, providing a favorable safety profile and effective disease control.